METADATA ADMINISTRATION FOR HEALTH CARE DATA AMALGAMATION - MD. ANWAR (International Journal of Multidisciplinary Research and Studies, 2020)
The lack of fine-grained, cross-cohort query, and exploration interfaces and systems. Although many data repositories allow users to browse their content, few support fine-grained, cross-cohort query, and exploration at the study-subject level. To understand the challenge, we provide a review of the key concepts. In clinical research, investigators tend to work independently or in clusters of research teams. Raw data collected from experiments or clinical trials are usually stored electronically on a computer. However, to perform independent analysis or verify experimental results, sharing data between different researchers or teams is necessary. Furthermore, sharing and reuse of data is important for facilitating scientific discovery and enhancing research reproducibility.